Market frictions as building blocks of an organizational economics approach to strategic management - Mahoney, Joseph T.; Qian, Lihong (Strategic Management Journal, 2013)
This paper shows that market frictions are fundamental building blocks for an organizational economics approach to strategic management. Various organizational economic approaches (transaction costs, property rights, real options, and resource‐based) have distinctive focal problems and emphasize different combinations of market frictions. A wider recognition of the role of market frictions is useful for three main objectives. First, it helps identify an evolving market‐frictions paradigm in strategic management. Second, it shows how two primary questions in strategy of why firms exist and why some firms outperform others and the three primary strategic goals of cost minimization, value creation, and value capture can be better joined and evaluated. Third, different combinations of market frictions can generate new research questions and advance theory development in the strategic management field . Copyright © 2013 John Wiley & Sons, Ltd.